Stratification of complexity in congenital heart surgery: comparative study of the Risk Adjustment for Congenital Heart Surgery (RACHS-1) method, Aristotle basic score and Society of Thoracic Surgeons-European Association for Cardio- Thoracic Surgery (STS-EACTS) mortality score - Cavalcanti,Paulo Ernando Ferraz (2015)
AbstractObjective:To determine whether stratification of complexity models in congenital heart surgery (RACHS-1, Aristotle basic score and STS-EACTS mortality score) fit to our center and determine the best method of discriminating hospital mortality.Methods:Surgical procedures in congenital heart diseases in patients under 18 years of age were allocated to the categories proposed by the stratification of complexity methods currently available. The outcome hospital mortality was calculated for each category from the three models. Statistical analysis was performed to verify whether the categories presented different mortalities. The discriminatory ability of the models was determined by calculating the area under the ROC curve and a comparison between the curves of the three models was performed.Results:360 patients were allocated according to the three methods. There was a statistically significant difference between the mortality categories: RACHS-1 (1) - 1.3%, (2) - 11.4%, (3)-27.3%, (4) - 50 %, (P<0.001); Aristotle basic score (1) - 1.1%, (2) - 12.2%, (3) - 34%, (4) - 64.7%, (P<0.001); and STS-EACTS mortality score (1) - 5.5 %, (2) - 13.6%, (3) - 18.7%, (4) - 35.8%, (P<0.001). The three models had similar accuracy by calculating the area under the ROC curve: RACHS-1- 0.738; STS-EACTS-0.739; Aristotle- 0.766.Conclusion:The three models of stratification of complexity currently available in the literature are useful with different mortalities between the proposed categories with similar discriminatory capacity for hospital mortality.